Well-posedness for parametric optimization problems with variational inclusion constraint. (2nd April 2016) - Chuang, Chih-Sheng
Abstract : In this paper, we study the well-posedness for the parametric optimization problems with variational inclusion problems as constraint (or the perturbed problem of optimization problems with constraint). Furthermore, we consider the relation between the well-posedness for the parametric optimization problems with variational inclusion problems as constraint and the well-posedness in the generalized sense for variational inclusion problems.